Faktor-Faktor Yang Mempengaruhi Kunjungan Lanjut Usia Ke Posyandu Lanjut Usia Desa Tegalgiri Nogosari Boyolali - Susilowati, Susilowati; , Agus Sudaryanto, S.Kep., Ns., M.Kes; , Ambarwati, S.Pd. M.Si (2014)
Abstract background: the biological development of the elderly is to be experienced by all people naturally. In the process of aging, the elderly decreased organ function or highly susceptible to the disease, therefore it means much-needed health services in this age period. Researchers focus on the elderly because posyandu integrated elderly services are heading for seniors, it‟s effectively used as a means of health facilities for the elderly and to monitor and maintain the health status of the elderly. Therefore, the elderly are expected to visit and be active in activities organised by the elderly posyandu in their areas respectively, so that the elderly get health services and health education to health needs at times of old. Objective: to know the factors (age, gender, occupation, level of education, family support, and attitude of the elderly) that affect the elderly visits to the elderly Posyandu in the village of Tegalgiri Nogosari Boyolali. Research methods: this research using quantitative techniques, with a cross sectional method. Sampling techniques using proportional stratified sampling with amount of sample are 79 respondents. Test analysis of this research data using statistical test of Chi Square. Research results: 1) there is no relation between the age (p= 0,295) and the sexes (p= 0,275) with the elderly visits to elderly Posyandu. 2) there is a relationship between work (p= 0,027), the level of education (p= 0,037), attitudes (p= 0,005), and family support (p= 0,001) with the elderly visits to elderly Posyandu. Conclusion: the results of statistical tests indicate that there is a relationship between employment, level of education, attitude, and support families with the elderly visits to elderly Posyandu.